PELATIHAN FOTOGRAFI DAN CITRA DIGITAL UNTUK MENINGKATKAN KUALITAS KONTEN DIGITAL AKUN BISNIS UMKM RUSUNAWA WONOREJO, SURABAYA - Romi Ilham; Lindiawati Lindiawati; Dewi Ayu Wulandari; Yudha Delonix; Renzina Renzina; Heri Supriyanto (-, 2023)
The problem challenged by MSMEs in ‘Rusunawa’ ( a rented simple flat belonging to the local government of Surabaya), at Wonorejo, Rungkut District, Surabaya is the low market response due to the lack of the quality of photos of MSME products as digital content. Therefore the solution offered is learning and practicing photography and digital image. The output of the activity is photos and edited photos and digital product catalogs uploaded on social media (Instagram, WhatsApp Status, and WhatsApp Business). After the training, participants are  able to create product photos for digital content. product photos made by the support  of a mini studio, properties that support the technique of taking the right angle and lighting. In addition, participants were also able to edit photos with the applications of  Photorrom and Canva. Assistance of the Team is provided by monitoring the quality of photos taken and shared on WAG. After the photo is considered good, then it will be uploaded as content on Instagram or on WA Business.